The perceived usefulness of E-recruitment among the jobseekers in Malaysia / Ernie Syazana Noor - Noor, Ernie Syazana (Faculty of Business and Management, 2009)
In this current economic climate, many people are searching for jobs from Internet-based (online) recruitment service providers. Online recruitment has become an effective way to reach the majority of candidates globally. The purpose of this paper is to determine the perceive usefulness of e-recruitment services among jobseekers in Malaysia and to test whether the behavior intention towards E-recruitment services. A survey was conducted pertaining to the objective of these research in perceived usefulness of E-recruitment services and the pattern of behavior intention among the jobseekers .A framework was drawn to linkage between the perceived usefulness and ease of use towards the behavior intention. This paper’s conceptual model and specific objective were tested using a sample of 50 respondents from the jobseekers in the area of Kuala Lumpur. This study will benefit the recruitment service providers or other business organizations in improving their recruitment website hence the users would have positive perception towards online recruitment system.